2017
DOI: 10.1002/lary.27036
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic sentinel lymph node biopsy using indocyanine green‐neomannosyl human serum albumin

Abstract: NA. Laryngoscope, 128:E135-E140, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Organic nanocarriers for ICG are nature nanoparticles, such as serum albumin (albumin human, AH) [ 51 , 52 ]. ICG binding to albumin results in the improvement of its characteristic as a fluorescent marker — its fluorescent intensity increases.…”
Section: Theranostic Approachmentioning
confidence: 99%
“…Organic nanocarriers for ICG are nature nanoparticles, such as serum albumin (albumin human, AH) [ 51 , 52 ]. ICG binding to albumin results in the improvement of its characteristic as a fluorescent marker — its fluorescent intensity increases.…”
Section: Theranostic Approachmentioning
confidence: 99%
“…Previous preclinical studies have reported the superiority of MSA-ICG compared to ICG alone for SLN detection in porcine lung cancer model 40 , porcine esophageal cancer model 41 , and mouse tongue cancer model 42 . In these studies, CD206 was expressed at a high level in the macrophages of SLNs, and MSA-ICG exhibited a higher binding affinity to CD206 than ICG alone.…”
Section: Introductionmentioning
confidence: 99%
“…The utility of ICG is based on the properties of functional uptake in the lymph nodes via the lymphatics, radio-opacity on imaging and fluorescence when visualized at surgery. While the scope of literature regarding ICG use for management of head and neck cancer is small in comparison to other anatomic locations, one theme in initial studies is to investigate hybrid approaches in which ICG is combined with other contrast mechanisms such as 99 Tc [ 8 12 ]. Here, we investigate a new hybrid approach using ICG fluorescence combined with intraoperative cone-beam CT (CBCT) imaging.…”
Section: Introductionmentioning
confidence: 99%